Effect of sex hormones level on the external genital tract infection in pregnant and non- pregnant women in Thi-Qar governorate, Iraq - Abdul wehab wajeh , Safa; Abdul Hussein , Basim; Abdul Razzaq, Mohanad (University of Thi-Qar Journal of Science, 2018)
The current study was conducted in Dhi Qar governorate, Iraq to determine the main types of microorganisms that cause female genital tract infection and the extent of the effect of the level of  sex  hormones (prolactin, progesterone, estrogen) on the presence of infection , 245 samples were collected for both vaginal swabs and blood  (where take  a vaginal swab and  blood from every woman) , where 150 women were  pregnant  and 95 women  non-pregnant women , aged 16-45 years . Among non-pregnant women, most were women who had a reproductive tract infection within the leuteal phases , where our study included 58 women at leuteal phase , 20 women were in follicular phase , 17 women within ovulation phase of the menstrual cycle .The study showed that Candida albicans , Staphylococcus aureus , Escherichia coli , Gardnerella vaginalis , Klebsiella pneumonia , Staphylococcus epidermids , Enterobacter cloaceae were isolated from women in follicular phase , the diversity of infections was lower in women in the ovulation stage, where they were isolated only Candida albicans , Staphylococcus aureus , Escherichia coli , Gardnerella vaginalis ,and from women with leuteal phase was obtained Candida albicans , Staphylococcus aureus , Escherichia col ,Gardnerella vaginalis , Klebsiella pneumonia , Staphylococcus epidermids , Proteus mirabilis, Pseudomonas aeruginosa  , the precence of all type of pathogens in our study  was associated with elevated estrogen and progesterone levels except  the growth of Staphylococcus epidermids , Proteus mirabilis, Pseudomonas aeruginosa.